Drosophila Motor Neuron Retraction during Metamorphosis Is Mediated by Inputs from TGF-beta/BMP Signaling and Orphan Nuclear Receptors. - Boulanger, A.; Farge, M.; Ramanoudjame, C.; Wharton, K.; Dura, J.M. (PLoS ONE, 2012)
Larval motor neurons remodel during Drosophila neuro-muscular junction dismantling at metamorphosis. In this study, we describe the motor neuron retraction as opposed to degeneration based on the early disappearance of ?-Spectrin and the continuing presence of Tubulin. By blocking cell dynamics with a dominant-negative form of Dynamin, we show that phagocytes have a key role in this process. Importantly, we show the presence of peripheral glial cells close to the neuro-muscular junction that retracts before the motor neuron. We show also that in muscle, expression of EcR-B1 encoding the steroid hormone receptor required for postsynaptic dismantling, is under the control of the ftz-f1/Hr39 orphan nuclear receptor pathway but not the TGF-? signaling pathway. In the motor neuron, activation of EcR-B1 expression by the two parallel pathways (TGF-? signaling and nuclear receptor) triggers axon retraction. We propose that a signal from a TGF-? family ligand is produced by the dismantling muscle (postsynapse compartment) and received by the motor neuron (presynaptic compartment) resulting in motor neuron retraction. The requirement of the two pathways in the motor neuron provides a molecular explanation for the instructive role of the postsynapse degradation on motor neuron retraction. This mechanism insures the temporality of the two processes and prevents motor neuron pruning before postsynaptic degradation.